Visual Rehabilitation after Phacoemulsification with Rigid Intraocular Lens Implantation at Tertiary Care Hospital-Jamshoro - Mahesar, Mona Liza; Ahmed, Noman; Jatoi, Asadullah; Nasrani, Ashok Kumar (Pakistan Armed Forces Medical Journal, 2022)
Objective: To evaluate the visual rehabilitation after phacoemulsification with rigid intraocular lens implantation. Study Design: Prospective longitudinal study. Place and Duration of Study: Institute of Ophthalmology, Liaquat University of Medical and Health Sciences, Jamshoro Pakistan, from Jul to Dec 2020. Methodology: Ninety-four subjects diagnosed with unilateral cataracts were evaluated completely. Subjects with any other ocular disease were excluded from the study. Pre-operative and post-operative, surgical and visual outcomes along with follow-up of 4 weeks and 12 weeks best-corrected visual acuity, were recorded. Results: The mean age of study participants was 61.77±7.34 years. Post-operative complications were evaluated within one week of surgery. 22(23.4%) subjects showed striate keratopathy, 2(2.1%) indicated bullous keratopathy, and 7(7.4%) reported residual lens matter as a complication. The difference between good visual outcomes was 33(35.1%) within eight weeks (4th week till 12th week); similarly, the difference between satisfactory visual outcomes was 22(23.4%). The visual outcomes improved more than two folds after phacoemulsification with a rigid intraocular lens. Conclusion: The foldable intraocular lens is comparatively expensive and unaffordable for many patients in developing countries. Rigid IOL with phacoemulsification is a cost-effective method to remove cataracts and restore patient visual acuity.Accurate diagnosis, evaluation, and surgeon’s experience are important factors in achieving the required results.